Nanopartikel Perak dari Ekstrak Kulit Nanas: Potensi Antifungal terhadap Malassezia furfur ATCC 14521 - Eliya Mursyida; Yashi Putri Anjeli (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Malassezia furfur is a lipophilic fungus commonly found in tropical regions with high humidity, particularly on human skin. One of the diseases caused by this fungus is Pityriasis versicolor (tinea versicolor). Treatment for this condition typically involves the use of azole-based drugs, either topically or systemically. However, the emergence of azole-resistant Malassezia furfur strains has reduced treatment efficacy. Thus, the development of new antifungal agents is necessary, one of which utilizes nanotechnology such as biologically synthesized silver nanoparticles (AgNPs), which are environmentally friendly and utilize waste materials. Pineapple peel is a type of waste that contains active compounds like flavonoids, alkaloids, tannins, and saponins, which have the potential to inhibit the growth of Malassezia furfur. This study aimed to characterize the biosynthesis of silver nanoparticles from pineapple peel infusion and evaluate their antifungal activity against Malassezia furfur at optimal concentrations and durations. Using a post-test only with control group design, the research involved preparing pineapple peel infusion, synthesizing silver nanoparticles, characterizing them using UV-Vis spectrophotometry, and testing antifungal activity with the well diffusion method. The results indicated the formation of AgNPs, marked by a color change from yellow to dark yellow with wavelengths of 320-340 nm. Antifungal activity tests showed the largest inhibition zone at a 1:6 ratio (11 mm) and the smallest at a 1:2 ratio (2.38 mm). In conclusion, silver nanoparticles synthesized from pineapple peel infusion demonstrated antifungal activity against Malassezia furfur.